Speaking Anxiety Experienced By Indonesian Students In An International University - Misnariah Idrus (Universitas Negeri Makassar, 2022)
Systematic and analytical investigations on foreign language communication anxiety outside the language training classroom context have important implications for language use. For instance, Guntzviller et al. (2016) stated that a study in that context will enhance the understanding on the emergence of negotiation with the multilingual environment in the foreign speaker’s everyday lives. Unfortunately, there seems to be a dearth in studies in the context mentioned earlier. Even if the studies discussed formerly could give an insight into how anxiety affects the performance of the second language use in the real word settings, they highly likely cannot be applied to the use of L2 in the academic environment. The primary objectives of this research are to investigate the extent to which Indonesian students experience speaking anxiety in the academic speaking context and internal factors promoting them. This study employed qualitative approach to explore the subjective opinions, experiences, and feelings of respondents (Dornyei, 2007) related to the research question. Based on the data obtained from the three data collection methods (reflective journal, Focus Group Discussion, and interview), the extents to which the speaking anxiety occur and internal factors promoting it were found varied. Keywords: Speaking anxiety, Indonesian students, internal factors